The Implementation of the Philosophical Values of Rukun, Raket, Regeng, and Rumekso in the Javanese Diaspora Community: An Ethnographic Study of the Pujakesuma Extended Family Association in Medan - Saif Arrasid Saif; Abrar M Dawud Faza (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangka Raya, 2026)
This study aims to conduct an in-depth examination of the implementation of the philosophical values of Rukun, Raket, Regeng, and Rumekso (4R) as the basis of social ethics within the Paguyuban Keluarga Besar Pujakesuma, a community of Javanese migrants in Sumatra. This study addresses the limited empirical research linking local values to social practices within diaspora communities. The research employs a qualitative approach using ethnographic methods, including participant observation, in-depth interviews, and document analysis. The findings reveal that the value of Rukun functions as a normative mechanism for maintaining harmony through consensus-based deliberation; Raket strengthens affective cohesion through intense interpersonal relationships; Regeng manifests in social solidarity practices rooted in collective action; while Rumekso serves as an ethical foundation for fostering empathy and social sensitivity. These four values operate not only as cultural symbols but also as an adaptive value system in responding to the dynamics of life in the diaspora community. Their implementation has proven capable of strengthening social cohesion, increasing collective participation, and maintaining the sustainability of cultural identity. Thus, this study offers conceptual and empirical contributions to enriching the study of cultural sociology, particularly regarding the transformation of local values in the context of contemporary society.